QUALITATIVE INDICATOR OF GROWTH OF SEGMENTS OF NETWORK WITH DIFFERENT SERVICE DISCIPLINES - A. G. Kostukovsky (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
Obtained by assessing the quality of telecommunication channels in a first approximation, provide a new estimate the growth of the telecommunication network in a mixed load by matching between a power network in the segment circuit and power network segment packet-switched in units (Kbit/sec) × km. This comparison allows operators to better navigate in what segment of the network, you must first invest capital investments for its development. And how does this compare with the development of the tariff plans that display the quality of competing services.